Optimization Design Learning Language English Based Digital - Manda, Ibrahim; Hermansyah, Sam (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
The time of the Covid-19 pandemic is not yet end create atmosphere Study become more limited. Learning digital based no can avoided for the sake of creation continuity activity education. Teacher as provider, teacher and evaluator on process learning must always internal skill upgrades face reality participant increasingly educated _ fed up will situation condition limitations patterns, media as well access learning. devotion to public This give contribution to language teachers English in the district Sidrap the joined into the English Subject Teacher Conference (MGMP). which method used in activity This in the form of workshops and assistance around design learning Language English digitally based _ material regarding IT literacy teachers, use application KineMaster deep _ prepare learning videos creative, use of assessment platforms through application dojo class and creation of creative E-books with application flip book maker. End from activity accompaniment here, language teacher English can create a learning e-book used in teach and do evaluation to participant educate more online classes interesting and innovative so that presentation material learning can optimal.